2013
DOI: 10.1155/2013/219817
|View full text |Cite
|
Sign up to set email alerts
|

Objectifying Acupuncture Effects by Lung Function and Numeric Rating Scale in Patients Undergoing Heart Surgery

Abstract: Rationale. Poststernotomy pain and impaired breathing are common clinical problems in early postoperative care following heart surgery. Insufficiently treated pain increases the risk of pulmonary complications. High-dose opioids are used for pain management, but they may cause side effects such as respiratory depression. Study Design. We performed a prospective, randomized, controlled, observer-blinded, three-armed clinical trial with 100 patients. Group 1 (n = 33) and Group 2 (n = 34) received one 20 min sess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“… 1 , 4 , 6 , 7 In this analyses, not only patient-reported outcome measures showed improvement, but also standardized measures (eg, lung function in the study on postmastectomy pain). 6 As a comparator, sham acupuncture was implemented. In those arms, every patient also received an acupuncture treatment, but the needles were not inserted as deeply as in real acupuncture and the acupoints did not lay on the traditional given “pathways.”…”
Section: Discussion and Future Trial Designmentioning
confidence: 94%
See 2 more Smart Citations
“… 1 , 4 , 6 , 7 In this analyses, not only patient-reported outcome measures showed improvement, but also standardized measures (eg, lung function in the study on postmastectomy pain). 6 As a comparator, sham acupuncture was implemented. In those arms, every patient also received an acupuncture treatment, but the needles were not inserted as deeply as in real acupuncture and the acupoints did not lay on the traditional given “pathways.”…”
Section: Discussion and Future Trial Designmentioning
confidence: 94%
“…Sham acupuncture control arms seem to be a valid comparator, and the Shanghai group has shown that this can work effectively in a prospective randomized trial 27 . Other groups have also supported this evidence, but not necessarily with cancer patients but with postmastectomy pain, sinusitis, or osteoarthritis 1, 4, 6, 7. In this analyses, not only patient-reported outcome measures showed improvement, but also standardized measures (eg, lung function in the study on postmastectomy pain) 6 .…”
Section: Discussion and Future Trial Designmentioning
confidence: 95%
See 1 more Smart Citation
“…Depending on the treatment arm either verum or sham acupuncture will be applied [ 23 , 24 , 26 , 28 , 30 , 31 ]. Acupuncture will be performed after treatment bi-weekly during the first week of RT, thereafter weekly until the end of RT.…”
Section: Methodsmentioning
confidence: 99%
“…The previously mentioned studies show that acupoints’ diagnosis-dependent selection contributed to a higher analgesic effect. If acupoints are understood as reflex points that elicit specific neurovegetative changes, it can be speculated that they might only yield satisfactory treatment results if they match the current vegetative status of the patient [ 23 ]. In some cases, the variability between practitioners’ evaluations must be considered [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%